2021
DOI: 10.1001/jamapsychiatry.2021.1818
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Mood Disorders and Risk of COVID-19 Infection, Hospitalization, and Death

Abstract: Preexisting noncommunicable diseases (eg, diabetes) increase the risk of COVID-19 infection, hospitalization, and death. Mood disorders are associated with impaired immune function and social determinants that increase the risk of COVID-19. Determining whether preexisting mood disorders represent a risk of COVID-19 would inform public health priorities.OBJECTIVE To assess whether preexisting mood disorders are associated with a higher risk of COVID-19 susceptibility, hospitalization, severe complications, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
162
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(194 citation statements)
references
References 87 publications
9
162
0
Order By: Relevance
“…Previous systematic reviews and meta-analyses have shown an elevated risk for COVID-19-related morbidity and mortality in people with mental disorders ( 8 – 10 , 29 ). This is added on top of an already decreased life span of about 20 years for people suffering from severe mental illness ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews and meta-analyses have shown an elevated risk for COVID-19-related morbidity and mortality in people with mental disorders ( 8 – 10 , 29 ). This is added on top of an already decreased life span of about 20 years for people suffering from severe mental illness ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among mental health disorders evaluated in one study, schizophrenia spectrum disorder was shown to be related to mortality among patients with COVID-19 though an association was not seen among patients with mood or anxiety disorders ( 27 ). Additionally, a large-scale meta-analysis did not find a relationship between preexisting mood disorders and risk for infection, hospitalization and death ( 28 ). In contrast, a recent analysis of COVID-19 infection and mortality found the odds of mortality was 2.78 times greater among patients testing positive who had a history of mood disorders ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have noted the bidirectional link between COVID-19 and mental illness; COVID-19 elevates risk of mental illness and mental illness elevates the risks of COVID-19 (Taquet et al 2021;Wang et al 2021). A recent meta-analysis has robustly demonstrated that pre-existing mood disorders are associated with higher rates of hospitalisation and death from COVID-19 infection (Ceban et al 2021). Additionally, individuals with mental illness requiring inpatient or residential care, by virtue of congregated living and difficulty in adherence to risk mitigation strategies can be at increased risk of exposure and transmission of COVID-19 (Kozloff et al 2020).…”
Section: Mental Health and Societal Impacts Of Covid-19mentioning
confidence: 99%